1960
DOI: 10.1161/01.cir.21.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Arteriosclerosis Obliterans: Review of 520 Cases with Special Reference to Pathogenic and Prognostic Factors

Abstract: The clinical and follow-up data on 520 non-diabetic patients less than 60 years of age who had a clinical diagnosis of arteriosclerosis obliterans of the lower extremities made at the Mayo Clinic in the period 1939 through 1948 were reviewed from the standpoint of pathogenesis, prognosis, and clinical course of the disease. The ratio of males to females was 11 to 1, and the mean concentration of plasma cholesterol in the male patients with arteriosclerosis obliterans was approximately 50 mg. per 100 ml. greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
1
7

Year Published

1967
1967
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(76 citation statements)
references
References 0 publications
8
60
1
7
Order By: Relevance
“…Symptoms of hand ischemia are more frequent in diabetics and smokers (17)(18)(19)(20)(21). Commonly encountered symptoms include cold hand, numbness, and hand pain on and/or off dialysis.…”
Section: Clinical Features and Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of hand ischemia are more frequent in diabetics and smokers (17)(18)(19)(20)(21). Commonly encountered symptoms include cold hand, numbness, and hand pain on and/or off dialysis.…”
Section: Clinical Features and Differential Diagnosismentioning
confidence: 99%
“…Both current and former smoking is associated with peripheral arterial disease (17,18). In addition, smoking increases the risk for amputation in patients with claudication (19) and decreases patency rates after lower extremity bypass (20). It has been demonstrated that in dialysis patients, current smoking is predictive of peripheral arterial disease and future cardiovascular events (21).…”
Section: Management Proposal For Dhismentioning
confidence: 99%
“…In a series of 520 cases Juergens et al found male to female ratio of 11:1 [5]. In epidemiological study by Jelnes et al have consistently reported gender prevalence ratio of less than 2:1 [6].…”
Section: Asmentioning
confidence: 95%
“…1 However, lesions of a significant part of the large artery system, such as arteriosclerosis obliterans of the lower limbs, may have general consequences on circulatory dynamics. Indeed, the large arteries act as a reservoir that stores blood during cardiac ejection and re-leases it during diastole, enabling the intermittent cardiac output to be converted to a steady flow through the capillaries.…”
Section: (Arteriosclerosis 2:266-271 May/june 1982)mentioning
confidence: 99%